The medium is the massage: An inventory of effects - Fiore, Quentin; McLuhan, Marshall (Madera Gingko Press, 2001)
Millions of "global villagers" connected by the communications revolution Marshall McLuhan foresaw, have never read the most influential, prophetic, and entertaining book ever written on the subject--The Medium is the Message (originally published in 1967). The authors have selected excerpts from McLuhan's most electrifying theories and insights. By linking text with images, they created this mesmerizing, first-of-its kind book. Photos and illustrations.